A novel MoClo-mediated intron insertion system facilitates enhanced transgene expression in Chlamydomonas reinhardtii - Aschern, Moritz; Braad, Jochem; Milito, Alfonsina; Alzuria, David; Yang, Jae-Seong (Frontiers in Plant Science, 2025)
The Chlamydomonas Modular Cloning (MoClo) toolkit allows for straightforward and flexible construction of genetic modules for gene expression in the microalgal model species, fostering developments in algal biotechnology. Efficiently expressing transgenes from the nuclear genome of C. reinhardtii requires the proper insertion of introns throughout the respective gene, as it can substantially enhance the gene expression. To facilitate synthetic biology approaches in this microalga, we developed a novel strategy for intron insertion into synthetic DNA fragments. Our method aligns with current MoClo standards, and its feasibility is demonstrated by assembling genes of various lengths and successfully expressing them in C. reinhardtii. Examples include enhanced NanoLuc expression with increased intron numbers, a fungal luciferase enabling bioluminescence in C. reinhardtii, and a fungal tryptophan decarboxylase.